Narasi sejarah yang tidak setara: mengurangi bias gender dalam buku teks sejarah Indonesia - Utama, Taqwa Ridlo (Universitas Negeri Malang, 2024)
Abstract Gender bias in Indonesian history education remains a significant issue that requires attention. This research aims to reduce such disparities by exploring the often-overlooked representation of women's roles. Using a descriptive qualitative method and a literature review approach, this study analyzes the historiography dominated by patriarchal perspectives in 10th-grade high school history textbooks, specifically on the topic of the Islamic kingdoms in Indonesia. The implementation of feminist pedagogy is carried out to highlight the issue of gender inequality in historical narratives. The analysis is conducted within the framework of cultural feminism, exploring Indonesian values and culture to enrich women's narratives. Prominent female figures in leadership, military, politics, law, and economics are highlighted to create a more inclusive narrative. The findings of this study are expected to contribute to the development of gender-sensitive teaching materials that align with a more flexible and contextual curriculum paradigm. Abstrak Bias gender dalam pendidikan sejarah Indonesia masih menjadi isu signifikan yang memerlukan perhatian. Penelitian ini bertujuan untuk mengurangi ketimpangan tersebut dengan mengeksplorasi representasi peran perempuan yang sering terabaikan. Menggunakan metode kualitatif deskriptif dan pendekatan studi pustaka, penelitian ini menganalisis historiografi yang didominasi oleh perspektif patriarki dalam buku teks sejarah kelas X SMA pada materi tentang masa kerajaan Islam di Indonesia. Penerapan pedagogi feminis dilakukan untuk menyoroti isu ketidakadilan gender dalam narasi sejarah. Analisis dilakukan dalam kerangka feminisme kultural, menggali nilai-nilai dan budaya Indonesia untuk memperkaya narasi perempuan. Tokoh-tokoh perempuan yang berperan penting dalam bidang kepemimpinan, militer, politik, hukum, dan ekonomi diangkat untuk menciptakan narasi yang lebih inklusif. Temuan penelitian ini diharapkan dapat berkontribusi pada pengembangan bahan ajar berperspektif gender yang sejalan dengan paradigma kurikulum yang lebih fleksibel dan kontekstual.